2018
DOI: 10.1021/acs.jafc.8b04733
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Visual Detection of Benzoyl Peroxide in Food by a Colorimetric and Ratiometric Fluorescent Probe

Abstract: A coumarin-based fluorescent probe was prepared for rapid and visual detection of benzoyl peroxide. The probe could quantitatively determine benzoyl peroxide with fast response (<6 min), high sensitivity, and low limit of detection (163 nM). The probe exhibited good response toward benzoyl peroxide with a significant color change from blue to yellow along with fluorescence color alteration from red to blue. The probe determined benzoyl peroxide in real food samples (wheat flour, noodle, and dumpling flour) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…With the developed method, the ultrasensitive detection for BPO can be completed within a short time. In addition, the sensitivity of this method was higher than that of previous fluorescence methods [1,10,37,39] highlighting its potential use for BPO detection.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…With the developed method, the ultrasensitive detection for BPO can be completed within a short time. In addition, the sensitivity of this method was higher than that of previous fluorescence methods [1,10,37,39] highlighting its potential use for BPO detection.…”
Section: Resultsmentioning
confidence: 85%
“…We observed that the fluorescence intensity of PABA gradually decreased with increasing BPO concentration (Figure 5A) and the negative logarithm of BPO concentration was proportional to the quenching in PABA fluorescence intensity (F 0 –F i ) with a linear relationship of Y = −198.94 X + 1819.44 (R 2 = 0.9941) in the detection range of 8.26 × 10 −9 M – 8.26 × 10 −4 M (Figure 5B). The LOD is usually obtained from three times of signals to noise (S/N = 3) [8,35,36,37,38] and the estimated LOD was 1.06 × 10 −9 M, featuring a high sensitivity. With the developed method, the ultrasensitive detection for BPO can be completed within a short time.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table S2, there have been a variety of determination methods for BPO such as gas chromatography (GC) [28], high-performance liquid chromatography (HPLC) [29][30][31], capillary electrophoresis (CE) [32], the electrochemical method [33,34], chemiluminescence [35,36], and the other optical methods [37][38][39][40][41]. To discover the presence of BPO easily and quickly, further efforts are necessary to develop real-time methods, including colorimetric determination.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive BPO not only has great safety hazards in the production of flour, but does not guarantee the actual nutritional value of flour, and even endangers people's health. On the one hand, excessive BPO destroys the nutrients in the flour, such as beta-carotene and vitamins, reducing body absorption (Hu et al 2018). On the other hand, when an excessive amount of BPO enters the human body, it decomposes into a highly dangerous oxidative free radical and converts it into a harmful substance (such as benzoic acid) that is detoxified by the liver, thereby causing liver damage (Abe-Onishi et al 2004;Wu et al 2019;Ponhong et al 2015).…”
Section: Introductionmentioning
confidence: 99%